Japan a pictorial interpretation (Tokyo, 1932)
The Japan of pagodas and cherry blossms, of beautiful scenes and ancient temples, which rightly attracts the tourist has been, and is being, adequately presented to the world. One which showed Japan as a foreign resident comes to see it a land confused by opposing forces, of adaptation and imitation of great success and some failures, Oriental and Western an ancient civilization struggling with modern materialism a nation at the crossroads.